An Fem Study of Die Attach Packaging Effect on Nanomechanical Si Optical Filters - Seok, Seonho; Hah, Dooyoung (Institute of Electrical and Electronics Engineers Inc., 2017)
This paper presents a finite element analysis of die attach packaging stress effect on emerging nanomechanical silicon optical filters. The proposed silicon optical filter is composed of Si waveguides and a microring resonator having a few hundred nm in thickness and a few tens of μm in length. Photonic integrated circuit is typically implemented by attaching a new component to a common ceramic interposer with other components. Such an attachment process would be a cause of unwanted performance deviation of MEMS or NEMS devices due to the packaging stress. Therefore, an FEM model has been used to evaluate deflection and stress of NEMS waveguides and microring resonators which are main elements for the proposed optical filter. © 2017 Elsevier B.V., All rights reserved.
CMP; CNRS; et al.; IEEE Components, Packaging and Manufacturing Technology Society (CPMT); IMS-BORDEAUX; LIRMM
Keywords: Die Attach; Fem (Finite Element Method); MEMS; Nems; Packaging; Silicon Optical Filter; Bandpass Filters; Ceramic Materials; Finite Element Method; MEMS; Nems; Optical Filters; Optical Resonators; Packaging; Resonators; Silicon; Waveguides; Attachment Process; Deflection and Stress; Die-Attach; Fem (Finite Element Method); Microring Resonator; Packaging Effects; Packaging Stress; Photonic Integrated Circuits; Waveguide Filters